Real coupling of solid oxide fuel cells with a biomass steam gasifier: Operating boundaries considering performance, tar and carbon deposition analyses. (15th May 2022) - Pongratz, Gernot; Subotić, Vanja; von Berg, Lukas; Schroettner, Hartmuth; Hochenauer, Christoph; Martini, Stefan; Hauck, Maximilian; Steinruecken, Benjamin; Skrzypkiewicz, Marek; Kupecki, Jakub; Scharler, Robert; Anca-Couce, Andrés
Graphical abstract: Highlights: Real coupling of biomass gasifier with solid oxide fuel cells for dozens of hours. Stable operation for 30 h at 800 and 850°C when heavier tars are removed. Metal dusting of nickel mesh and zirconia-based anode when using raw product gas. Almost complete conversion of tars and benzene in the fuel cells at 800 and 850°C. Change from pyrolytic to graphitic carbon deposition between 800 and 850°C. Abstract: Solid oxide fuel cells are a promising alternative to gas engines for combined heat and power production based on biomass gasification. The technical complexity of realizing gasifier – fuel cell couplings has limited the number of experiments conducted in the past. However, results from such experiments are of high importance for the evaluation of tar thresholds and operating conditions ensuring a stable operation of fuel cells. For the first time, it was possible to demonstrate for dozens of hours the operation of solid oxide fuel cells with real product gas from steam gasification with a steam-to-carbon ratio of 2 and a typical tar content for fluidized bed gasification. Four coupling experiments with industrial-relevant cell designs were conducted, demonstrating a stable operation for 30 h without structural degradation of the anodes for cells with nickel/ceria- and nickel/zirconia-based anodes at 800°C and 850°C, if heavy tars were partially removed (2.8–3.7 g·Nm −3 gravimetric tars). Raw gas operation (4.6–4.8 g·Nm −3 gravimetric tars) led to metal dusting effects on nickel contact meshes and nickel/zirconia-based anodes, whereas nickel/ceria-based anodes were less affected. Carbon deposited on the alumina support in all experiments whereby a change from pyrolytic to graphitic structure could be observed when increasing the temperature from 800°C to 850°C, thus significantly reducing the risk for blockages in the flow channels. Moreover, high tar and benzene conversion rates were observed. Concluding, operating temperatures of 850°C and the removal only of heavy tars can enable stable long-term operation with a tar-laden steam gasifier product gas, even without increasing the steam-to-carbon ratio to values exceeding two.